Synthesis and characterization of maghemite nanoparticles deposited on silicon substrate / Nurul Athirah Abu Hussein - Nurul Athirah, Abu Hussein (2018)
This study comprised of two stages. In the first stage, pure maghemite nanoparticles within the size range of 10 nm were synthesized where at the second stage, the as-synthesized maghemite nanoparticles were deposited on silicon substrate and annealed at different temperature. In the first stage, the effect of varying ferric nitrate concentration (0.1, 0.3, 0.5, 0.7 and 1.0 M) on the size and magnetic properties of iron oxide nanoparticles were investigated. From X-ray diffraction analysis (XRD), the peaks and the lattice parameter obtained indicated that the nanoparticles formed were maghemite (γ-Fe2O3). It was then further confirmed by Raman analysis. The magnetization curve pointed out that the particles were super paramagnetic nanoparticles as there were no hysteresis loops found. The crystallite, magnetic and physical size of the nanoparticles were similar indicated that they were monocrystals. As the concentration of ferric nitrate increased from 0.1 M to 0.5 M, the size of the as-synthesized maghemite nanoparticles decreased. However, as the concentration of ferric nitrate was further increased, the size of the nanoparticles was increasing as well. This occurrence was due to the agglomeration of the high surface energy of the nanosized particles. The smallest size of the maghemite nanoparticles with the physical size of 6.90 nm was chosen for the next stage. In the second stage, 1 cm x 1 cm n-type silicon substrate was cleaned using RCA method. After that, 40 μl of the selected maghemite nanoparticles were deposited onto the silicon substrate using micropipette and were spin coated at 2500 rpm for 1 minute. The samples were then annealed at different temperatures which were 600°C, 700°C, 800°C and 900°C. The effects of different annealing temperatures were investigated. Physical characterizations were conducted through the analysis of x-ray diffractometer (XRD), raman analysis, atomic force microscopy (AFM) and electrical properties. XRD analysisiv revealed that the thin layer of maghemite nanoparticles on the silicon substrate was stable and was confirmed by Raman analysis. The thickness of the maghemite nanoparticles layer was investigated through AFM analysis. It was revealed that the thickness was approximately 25 nm. The maghemite nanoparticles were seen to be distributed homogeneously on the silicon substrate. The electrical properties of the samples were investigated through current density-electrical field (J-E) analysis. This study revealed that different annealing temperature yield a different electrical behaviour. This is mainly due to the grain size of the nanoparticles after annealing process, surface roughness behaviour, distribution and porosity of the nanoparticles, and also the thickness of the thin film maghemite nanoparticles.